The Impact of Fiscal Policy on Economic Growth in The Gambia - Touray, Katim; Botticelli, Tommaso; Sohna, Nasirou; Gubenko, Anastasia; Pratama, Obi (Universitas Bojonegoro, 2025)
The Gambia is a small country in West Africa that depends on tax revenue to fund her financial obligations and needs. In 2024, The Gambia hosted the second largest world gathering the OIC summit. Over the years, The Gambia was preparing for this event, and it incurred a lot of capital spending on infrastructure and other key areas. This research assesses the impact of fiscal policy (government spending) on the economy of the Gambia from 2010 to 2020. We obtained a time series data on GDP, Government expenditure, Tax revenue, export and Inflation and use OLS estimation to ascertain the relationship between Government expenditure and tax revenue of GDP Growth of The Gambia. Our findings shows that Government expenditure and tax revenue are significant contributors to GDP Growth in The Gambia from 2010 to 2020 and they are positively correlated to GDP Growth. Our findings also showed that export and inflation were not significant in the model. There is a limitation to our research due to unavailability of data, we were only focus from 2010 to 2020 future researcher on this domain can try expanding the period to see clearer picture of the relationship of fiscal policy variables on GDP Growth.